STRATEGI PEMBERDAYAAN UMKM DI PEDESAAN BERBASIS KEARIFAN LOKAL DI ERA INDUSTRI 4.0 MENUJU ERA SOCIETY 5.0 - Nugroho, Rusdi Hidayat; Andarini, Sonja (Jurnal Bisnis Indonesia, 2020)
Abstracs To overcome poverty in rural areas, namely by carrying out community empowerment to be independent, competitive and able to compete in the 4.0 industrial revolution era or the digital era and potentially contribute to national income. The presence of the industrial revolution 4.0 caused the impact of intense competition, MSMEs must be able to overcome these challenges creatively, product innovation, marketing, product packaging, human resource development and technology. In empowering MSMEs, a strategy for preparing economic empowerment in MSMEs is needed in the face of the era of the Industrial Revolution 4.0. The MSME empowerment strategy can be pursued through the Government's role in issuing fiscal and non-fiscal policies, the role of universities in carrying out services to educate and prosper the community, and the role of stakeholders encouraging MSMEs to become more independent and innovative Keywords: Strategy, Empowerment, UMKM, local wisdom Abstrak Untuk menanggulangi kemiskianan di Pedesaan yaitu dengan melaksanakan pemberdayaan masyarakat  agar bisa mandiri, kompetitif dan mampu bersaing  di era revolusi industri 4.0 atau era digital  serta berpotensi menyumbang pendapatan nasional. Hadirnya revolusi industri 4.0 menimbulkan dampak persaingan yang ketat, UMKM harus mampu mengatasi tantangan itu dengan kreatif, inovasi produk, pemasaran, kemasan produk, pengembagan sumber daya manusia dan Teknologi. Dalam pemberdayaan UMKM diperlukan strategi  penyiapan pemberdayaan ekonomi pada UMKM dalam menghadapi  era revolusi Infdustri 4.0. Strategi pemberdayaan UMKM dapat ditempuh melaui peran Pemerintah mengeluarkan kebijakan fiskal maupun non fiskal, Peran perguruan tinggi dalam melaksanakan pengabdian untuk mencerdaskan dan mensejahterakan masyarakat, dan Peran stekholder mendorong UMKM semakin mandiri dan inovatif Kata kunci : Strategi, Pemberdayaan, UMKM, kearifan lokal